2007
DOI: 10.1590/s1678-77572007000200013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental fluorosis in Bauru, São Paulo, Brazil

Abstract: Objective:To evaluate the prevalence of dental fluorosis in scholars aging 12 to 15 years old, residents in the city of Bauru, State of São Paulo, Brazil.Methods:1318 volunteers were enrolled in this study and examined in 18 public schools of the State of São Paulo. The examinations were performed in the schools' court by three dentists (with a Master's degree in Public Health), after toothbrushing supervised by another dentist. The teeth were dried with cotton pellets and examined under natural light by visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
1
14
1
8
Order By: Relevance
“…This result was higher than those reported in other studies, which obtained values ranging between 29.2% and 36% 13,14 , and the results reported by SB Brazil 2010 15 , which showed that the prevalence of fluorosis at age 12 was 16.7%. However, our results are similar to those of an epidemiological study in Teresina 16 .…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…This result was higher than those reported in other studies, which obtained values ranging between 29.2% and 36% 13,14 , and the results reported by SB Brazil 2010 15 , which showed that the prevalence of fluorosis at age 12 was 16.7%. However, our results are similar to those of an epidemiological study in Teresina 16 .…”
Section: Discussioncontrasting
confidence: 67%
“…There was an effect of fluorosis on the functional domain in both groups, as measured by the CPQ [8][9][10] and CPQ [11][12][13][14] . This domain examines issues mainly relating to chewing, which is the process of breaking and crushing of food using the posterior teeth (premolars and molars).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations